Design and methods for the training in exercise activities and motion for growth (TEAM 4 growth) trial: A randomized controlled trial. (15th July 2022) - Lambert, Linda M.; Pemberton, Victoria L.; Trachtenberg, Felicia L.; Uzark, Karen; Woodard, Frances; Teng, Jessica E.; Bainton, Jessica; Clarke, Shanelle; Justice, Lindsey; Meador, Marcie R.; Riggins, Jessica; Suhre, Mary; et al.
Abstract: Background: Growth is often impaired in infants with congenital heart disease. Poor growth has been associated with worse neurodevelopment, abnormal behavioral state, and longer time to hospital discharge. Nutritional interventions, drug therapy, and surgical palliation have varying degrees of success enhancing growth. Passive range of motion (PROM) improves somatic growth in preterm infants and is safe and feasible in infants with hypoplastic left heart syndrome (HLHS), after their first palliative surgery (Norwood procedure). Methods: This multicenter, Phase III randomized control trial of a 21-day PROM exercise or standard of care evaluates growth in infants with HLHS after the Norwood procedure. Growth (weight-, height- and head circumference-for-age z-scores) will be compared at 4 months of age or at the pre-superior cavopulmonary connection evaluation visit, whichever comes first. Secondary outcomes include neonatal neurobehavioral patterns, neurodevelopmental assessment, and bone mineral density. Eligibility include diagnosis of HLHS or other single right ventricle anomaly, birth at ≥37 weeks gestation and Norwood procedure at <30 days of age, and family consent. Infants with known chromosomal or recognizable phenotypic syndromes associated with growth failure, listed for transplant, or expected to be discharged within 14 days of screening are excluded. Conclusions: The TEAM 4 Growth trial will make an important contribution to understanding the role of PROM on growth, neurobehavior, neurodevelopment, and BMD in infants with complex cardiac anomalies, who are at high risk for growth failure and developmental concerns. Highlights: Evaluation of growth in single ventricle babies. A neurodevelopmental assessment. Passive range of motion to promote growth in single ventricle babies.